2020
DOI: 10.1016/j.heares.2020.107952
|View full text |Cite
|
Sign up to set email alerts
|

Noise-induced hearing loss in zebrafish: investigating structural and functional inner ear damage and recovery

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 108 publications
2
42
1
Order By: Relevance
“…This additional noise source can cause a reduction in animals' communication range and impair the detection of key signal features (insects: Klappert et al, 2009;fish: Ladich, 2013; amphibians: Bee and Swanson, 2007;birds: Lohr et al, 2003;marine mammals: Erbe et al, 2016;Rosa and Koper, 2018). Furthermore, anthropogenic noise can cause a wide range of effects, such as increased stress, behavioural avoidance, temporary threshold shifts, hearing loss or even death (Popper and Hastings, 2009;Barber et al, 2009;Shannon et al, 2015;de Jong et al, 2020;Breitzler et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This additional noise source can cause a reduction in animals' communication range and impair the detection of key signal features (insects: Klappert et al, 2009;fish: Ladich, 2013; amphibians: Bee and Swanson, 2007;birds: Lohr et al, 2003;marine mammals: Erbe et al, 2016;Rosa and Koper, 2018). Furthermore, anthropogenic noise can cause a wide range of effects, such as increased stress, behavioural avoidance, temporary threshold shifts, hearing loss or even death (Popper and Hastings, 2009;Barber et al, 2009;Shannon et al, 2015;de Jong et al, 2020;Breitzler et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the results of our analyses indicate that continuous noise affects hair cell loss in both male and female stone sculpins. The hair cell damage detected in this study likely resulted in hearing loss, as other studies had shown that hair cell damage led to a temporary threshold shift in fishes [91,108]. Furthermore, the previous study revealed the ultrastructural rearrangements in the olfactory receptor cells of Baikal sculpin males directed for the shutdown of pheromone perception during the paternal care period [109].…”
Section: Noise Causes Saccular Hair Cell Loss In Both Male and Female Stone Sculpinsmentioning
confidence: 61%
“…In other animal species, there are some scenarios in which an organism's reproductive axis has evolved sensitivity or insensitivity to the suppressive effects of stress [23,[116][117][118]. The testes of dominant males of the wild baboon, Papio spp., especially are less vulnerable to the disruptive effects of cortisol than those of subordinate males [108]. As in salmonids, glucocorticosteroid excess appears to play a role in programmed death [23].…”
Section: Noise Forces Accelerated Senescence Differently In Stone Sculpin Males and Femalesmentioning
confidence: 98%
“…In zebrafish and the closely related goldfish, exposure to high intensity noise at a low frequency (100 Hz) damages hair cells only in the posterior region of the saccular macula; exposure to middle frequencies (800-2000 Hz) damages hair cells in the middle of the saccule; and exposure to high frequency (4000 Hz) damages hair cells in the anterior. [103][104][105] The genetic and biophysical mechanisms underlying tonotopic organization in teleost fishes remain completely unknown.…”
Section: General Description Of Sensory Epitheliamentioning
confidence: 99%